Lactic Acid Production from Food Processing Wastes - Biswas, Rajarshi (My University, 2007)
A Lactobacillus plantarum culture (Lactobacillus plantarum MTCC2621) was characterized for its ability to degrade starch and consecutively produce lactic acid. The optimum starting pH and temperature were found to be pH 6 and 280C respectively. Under these conditions, the bacteria produced 1.58g/l of lactic acid after one day of growth. This lactic acid comes from the hydrolysis of starch, which was mediated by extracellular amylases. When the pH was controlled the lactic acid production was significantly increased yielding a value of 1.85g/l at a constantly maintained pH 6 and incubation temperature of 280C after a day of growth. L-lactate content of the produced lactic was quantified using a biochemical kit and it was found that the strain was actually producing a DL mixture of lactic acid with D:L ratio closely equals to 4:1. In the next phase of the experiments feasibility studies was carried out with a food processing effluent (a potato wash effluent, obtained from a snack food company). This study indicated that the strain could survive and grow, break down starch and produce lactic acid from the effluent.
Keywords: Lactic Acid Production; Hydrolysis of Starch